2012
DOI: 10.1590/s1983-51752012000200023
|View full text |Cite
|
Sign up to set email alerts
|

Retalho sural de fluxo reverso: 10 anos de experiência clínica e modificações

Abstract: Reverse flow sural flap: 10 years of clinical experience and changes Reverse-flow sural flap: 10 years of clinical experience and modifications Retalho sural de fluxo reverso: 10 anos de experiência clínica e modificações ABSTRACT Background: The reverse flow sural flap has been featured as a relevant option for reconstruction of the distal region of the legs and feet. However, some common mistakes are made while surgeons are learning how to employ this flap. The aim of this study was to analyze use of the fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 10 publications
(20 reference statements)
1
11
0
9
Order By: Relevance
“…Studies performed > 10 years ago showed a higher rate of complications (≤ 35%), with a significant reduction during the last 10 years (≤ 12%). 6 10 11 12 This fact was also reported by Vendramin et al, 13 who found different complication rates after evaluating the outcomes from the same surgical team at different periods of the learning curve. These literature findings do not agree with the present study, whose success rate was of 87.5%, since complications did not have any relation with the learning curve, as this technique was introduced in this service in 2001 and the complications occurred in 2009, 2013 and 2015.…”
Section: Discussionsupporting
confidence: 71%
“…Studies performed > 10 years ago showed a higher rate of complications (≤ 35%), with a significant reduction during the last 10 years (≤ 12%). 6 10 11 12 This fact was also reported by Vendramin et al, 13 who found different complication rates after evaluating the outcomes from the same surgical team at different periods of the learning curve. These literature findings do not agree with the present study, whose success rate was of 87.5%, since complications did not have any relation with the learning curve, as this technique was introduced in this service in 2001 and the complications occurred in 2009, 2013 and 2015.…”
Section: Discussionsupporting
confidence: 71%
“…The fasciocutaneous or fascial flaps of distal pedicle can be a good alternative to the distal regions, although this requires a good local circulation [2][3][4] . The microsurgical free flap has become a frequent indication.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…The use of skin grafts in these lesions is hampered by the scarce vascular bed and the poor granulation of wounds, often associated with prolonged exposure of deep structures, such as bone, tendon and blood vessel, and may be exacerbated by infections, as osteomyelitis [18]. There are many pedicled laps for soft tissue reconstruction in lower extremities (local fasciocutaneous laps, the sural lap or reverse sural lap, the gastrocnemius lap, the saphenous fasciocutaneous lap, the soleus or hemisoleus lap, the lateral supramalleolar lap, the perforator-based propeller lap) but the selection of the the laps depends on the avaibility of the donor sites, which are mainly located around the injured area [19][20][21][22][23][24][25][26][27]. Nowadays free-lap is the choice method to cover soft tissue defects in the distal third of the leg, but it has major disadvantages [28,29].…”
Section: Discussionmentioning
confidence: 99%